The relationship between alcohol use disorder and suicide in patients with obsessive compulsive disorder - Karaytuğ, Mahmut Onur; Tamam, Lut; Demirkol, Mehmet Emin; Namlıa, Zeynep (Journal of Dependence, 2023)
Objective: Data on the relationship between alcohol use disorder and suicide in patients with obsessive-compulsive disorder (OCD) are limited. The aim of this study was to investigate our hypothesis that there may be a relationship between alcohol use disorder and suicide in patients with OCD. Method: The study included 92 patients with OCD. General sociodemographic and clinical characteristics of the patients were evaluated. Yale-Brown Obsession Compulsion Scale (Y-BOCS) and Beck Suicidal Ideation Scale were administered to OCD patients. Results: The sample consisted of 54 women and 38 men. The rate of past suicide attempts was 19.6%. 16 patients were comorbid with Alcohol Use Disorder. Smoking, family history of mental illness and Beck Suicidal Ideation Scale score were significantly higher in the group with Alcohol Use Disorder. Smoking, alcohol use, family history of mental illness and Beck Suicidal Ideation Scale score were significantly higher in the group with suicide attempt. Conclusion: The results of this study showed that comorbid alcohol use disorder may be associated with past suicidal thoughts and attempts in patients with OCD. It may be appropriate to follow up OCD patients with alcohol use disorder more frequently in terms of suicide.